Coastal drowning: A scoping review of burden, risk factors, and prevention strategies. - William Koon; Amy Peden; Jasmin C Lawes; Robert W Brander (PLoS ONE)
Objective Coastal drowning is a global public health problem which requires evidence to support safety initiatives. The growing multidisciplinary body of coastal drowning research and associated prevention countermeasures is diverse and has not been characterised as a whole. The objective of this scoping review was to identify key concepts, findings, evidence and research gaps in the coastal drowning literature to guide future research and inform prevention activities. Methods We conducted a scoping review to identify peer reviewed studies published before May 2020 reporting either (i) fatal unintentional coastal drowning statistics from non-boating, -disaster or -occupational aetiologies; (ii) risk factors for unintentional fatal coastal drowning; or (iii) coastal drowning prevention strategies. Systematic searches were conducted in six databases, two authors independently screened studies for inclusion and one author extracted data using a standardised data charting form developed by the study team. Results Of the 146 included studies, the majority (76.7%) were from high income countries, 87 (59.6%) reported coastal drowning deaths, 61 (41.8%) reported risk factors, and 88 (60.3%) reported prevention strategies. Populations, data sources and coastal water site terminology in the studies varied widely; as did reported risk factors, which most frequently related to demographics such as gender and age. Prevention strategies were commonly based on survey data or expert opinion and primarily focused on education, lifeguards and signage. Few studies (n = 10) evaluated coastal drowning prevention strategies. Discussion Coastal drowning is an expansive, multidisciplinary field that demands cross-sector collaborative research. Gaps to be addressed in coastal safety research include the lack of research from lower resourced settings, unclear and inconsistent terminology and reporting, and the lack of evaluation for prevention strategies. Advancing coastal drowning science will result in a stronger evidence base from which to design and implement effective countermeasures that ultimately save lives and keep people safe.